Tungsten isotopic compositions of iron meteorites: Chronological constraints vs. cosmogenic effects - Markowski, A; Quitte, G; Halliday, A; Kleine, T (2006)
High-precision W isotopic compositions are presented for 35 iron meteorites from 7 magmatic groups (IC, IIAB, IID, IIIAB, IIIF, IVA, and IVB) and 3 non-magmatic groups (IAB, IIICD, and IIE). Small but resolvable isotopic variations are present both within and between iron meteorite groups. Variations in the 182W/184W ratio reflect either time intervals of metal-silicate differentiation, or result from the burnout of W isotopes caused by a prolonged exposure to galactic cosmic rays. Calculated apparent time spans for some groups of magmatic iron meteorites correspond to 8.5 ± 2.1 My (IID), 5.1 ± 2.3 My (IIAB), and 5.3 ± 1.3 My (IVB). These time intervals are significantly longer than those predicated from models of planetesimal accretion. It is shown that cosmogenic effects can account for a large part of the W isotopic variation. No simple relationship exists with exposure ages, compromising any reliable method of correction. After allowance for maximum possible cosmogenic effects, it is found that there is no evidence that any of the magmatic iron meteorites studied here have initial W isotopic compositions that differ from those of Allende CAIs [ε 182W = -3.47 ± 0.20 [T. Kleine, K. Mezger, H. Palme, E. Scherer and C. Münker, Early core formation in asteroids and late accretion of chondrite parent bodies: evidence from 182Hf-182W in CAIs, metal-rich chondrites and iron meteorites, Geochim. Cosmochim. Acta (in press)]. Cosmogenic corrections cannot yet be made with sufficient accuracy to obtain highly precise ages for iron meteorites. Some of the corrected ages nevertheless require extremely early metal-silicate segregation no later than 1 My after formation of CAIs. Therefore, magmatic iron meteorites appear to provide the best examples yet identified of material derived from the first planetesimals that grew by runaway growth, as modelled in dynamic simulations. Non-magmatic iron meteorites have a more radiogenic W isotopic composition than magmatic ones, even without cosmogenic corrections. This indicates that most of the IAB irons formed between 5 ± 3 and 11 ± 6 My after Allende CAIs. Similarly, the IIE irons formed between 9 ± 4 and 14 ± 5 My after the start of the solar system. Unlike IABs and IIEs, IIICDs do not show any resolvable W isotopic differences relative to Allende CAIs. © 2005 Elsevier B.V. All rights reserved.